Meanings of homophobia and life project for a homosexual student group - Dantas Silva, Washington Allysson (Revista de Psicologia, 2020)
Even with the development of societies, homophobia remains a persistent problem in contemporary times. There is much discussion about the person who discriminates, but there are a few discussions about the discriminated subject concerning this prejudice on their personal representation and its repercussions throughout his life. Therefore, given the relevance of this topic, this article aims to describe the meanings of homophobia and the life project for a group of homosexual university students. To this end, four students from different undergraduate courses of a public university in the northeast region of Brazil participated, who were invited to answer a series of questions about their sociodemographic characteristics and their personal perception about homophobia and its relationship with personal planning on the future. The narratives were explored through thematic content analysis. According to the group, homophobia is hostile behavior, motivated by the prejudice against homosexual behavior, but that does not directly affect the lives of its victims. These meanings are commented on according to the psychosocial consequences experienced by these subjects, such as the exclusion and need for egalitarian public policies. Keywords: Qualitative research; Social psychology; Homophobia; Prejudice.